2016
DOI: 10.1051/matecconf/20167010005
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sizing of Decentralized Photovoltaic Generation and Energy Storage Units for Malaysia Residential Household Using Iterative Method

Abstract: Abstract. World's fuel sources are decreasing, and global warming phenomena cause the necessity of urgent search for alternative energy sources. Photovoltaic generating system has a high potential, since it is clean, environmental friendly and secure energy sources. This paper presents an optimal sizing of decentralized photovoltaic system and electrical energy storage for a residential household using iterative method. The cost of energy, payback period, degree of autonomy and degree of own-consumption are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…They estimated that for 2010 it was around 40 US cents/ kWh and that it will fall to approximately 10 US cents/kWh by 2050. Rahman and Nordin [41] found that 14 US cents/kWh was the Cost of Energy for the optimal size of a residential PV system in Malaysia but including batteries in it.…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that for 2010 it was around 40 US cents/ kWh and that it will fall to approximately 10 US cents/kWh by 2050. Rahman and Nordin [41] found that 14 US cents/kWh was the Cost of Energy for the optimal size of a residential PV system in Malaysia but including batteries in it.…”
Section: Introductionmentioning
confidence: 99%